Jaringan Asosiasi dalam Penanganan Stunting di Kota Bandung - Malahina, Zefanya Agustinus; Wibowo, Hery; Yunita, Desi (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2026)
In Bandung City, stunting prevalence declined from 28.12% in 2019 to 12.4% in 2024 alongside improvements in nutrition surveillance and community outreach. This study examines how institutional networks shape stunting governance at the local level. Using a qualitative approach, data were collected through semi-structured interviews with government officials, health center staff, and community cadres, complemented by non-participant observations of coordination meetings and social network analysis of inter-institutional interactions. The findings indicate that strong ties among core government actors—Bappelitbang, the Health Office, and the Population and Family Planning Office—support stable coordination and consistent program implementation. Meanwhile, weak ties with external actors, including universities, religious organizations, and private sector partners, contribute additional resources and ideas, although engagement remains uneven. Health centers and community cadres function as bridging actors that translate policy into community-level action, particularly in early detection and nutrition education. The Task Force for Stunting Acceleration (TPPS) provides a formal platform that structures cross-sector collaboration. Overall, the study highlights the importance of balanced institutional linkages in enabling coordinated stunting interventions while acknowledging ongoing challenges related to capacity disparities and sectoral boundaries.